The Analysis of Translation Techniques of Irony and Sarcasm in Novel Entitled The Sign Of The Four - Rahmawati Sukmaningrum (ETERNAL (English Teaching Journal), 2016)
This research was aimed to identify the translation techniques used in translating the irony and sarcasm utterances in novel entitled The Sign of the Four and to find out the translation quality appearing as the effects of those translation technique applications. This research was an qualitative research. Data of this research were utterances or sentences in the novel The Sign of The Four which involves two different languages both the SL (English) and the TL (Indonesian). This research focused on product since the research questions were formulated to be answered based on the written texts which contain ironic and sarcasm utterances. Purposive sampling technique was choosen in choosing the data. The object of this research were ironic and sarcasm utterances, type of translation technique, and translation quality which cover accuracy, acceptability, and readibility of translated text English to Indonesia of novel The Sign of  The Four. The research findings reveal that the type of sarcasm found in The Sign of The Four novel are illocutionary sarcasm and proportional sarcasm. The sarcasm marker of iilocutionary sarcasm is the manner violation. While proportional sarcasm is characterized by self contradiction. When considering the context of the utterance, the sarcastic utterances are expressed by the actor, in order to insult his partner. The irony found in the novel is the ironical interjection characterized by the unusual collocation. Translation used in translating the ironic and sarcasm utterances in this novel are; reduction, amplification (addition), compensation, transposition, adaptation, discursive creation, and calque. The impact of the use of translation techniques is on the quality of the translated text. Acceptance of the translation is worth 3 (acceptable). Translation accuracy varies from 1 to 3 (from accurate to inaccurate).